Analysis of Using of Social Media as Communication for Lectures at PTKIN: Case Study of Da’wa Management of IAIN Sultan Amai Gorontalo and IAIN Pare-Pare - Perdana, Dian Adi; Asmar, Afidatul (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
Social media is a tool that cannot be separated from modern human life, regardless of age, location, profession, and status. Every message can be sent quickly and right to other people both short and far distances. The covid-19 outbreak makes everyone do social distancing to minimize the spread of the virus, including teaching and learning activities at schools and campuses. This research discusses social media that has used by students and lecturers in their online learning with various platforms directed by lectures or campus that occurred in students of the Da’wa Management department at IAIN Sultan Amai Gorontalo and IAIN Pare-Pare. This discussion aims to determine the analysis use the social media during the online learning period which has occurred in the last semester, so it will provide benefits to researchers and intellectuals to explore and learn effective ways of organizing online learning in the future. This study used a descriptive qualitative method that occurred in two different places (IAIN Sultan Amai Gorontalo and IAIN Pare-pare. The researcher collected data by observation, documentation, and interviews with several structured and non-structured questions. The data that has been collected and analyzed by the researcher to give conclusions from the problems that have been found. The results of this study indicate that the use of social media as communication for online lectures in the Da’wa Management Department of IAIN Sultan Amai Gorontalo and IAIN Pare-Pare is effective with several notes related to minor numbers on students' understanding of the material, personal enjoyment, influencing attitudes, social relations between students and lecturers. students and personal actions during the Covid-19 pandemic.